2006
DOI: 10.1002/dvdy.20898
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of vertebrate Protogenin (Prtg) and comparative expression analysis during axis elongation

Abstract: A murine cDNA encoding Protogenin, which belongs to the DCC/Neogenin family, was cloned in a screen performed to identify novel cDNAs regionally expressed in the neural plate. Isolation of the putative zebrafish orthologues allowed a comparative analysis of the expression patterns of Protogenin genes during embryogenesis in different vertebrate species. From mid-gastrulation to early somite stages, Protogenin expression is restricted to posterior neural plate and mesoderm, with an anterior limit at the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
(30 reference statements)
2
16
0
Order By: Relevance
“…In the chick spinal cord, Prtg expression is inversely correlated with Ascl1 expression, similar to what we have found in the retina (48). Prtg is a member of the DCC/Neogenin family (49,50) and contains four Ig and five fibronectin III domains in the extracellular domain. Ligands for Prtg have not been identified, and the intracellular domain does not share significant homology with the other four members of this family (DCC/Neogenin/Punc/Nope).…”
Section: Discussionsupporting
confidence: 85%
“…In the chick spinal cord, Prtg expression is inversely correlated with Ascl1 expression, similar to what we have found in the retina (48). Prtg is a member of the DCC/Neogenin family (49,50) and contains four Ig and five fibronectin III domains in the extracellular domain. Ligands for Prtg have not been identified, and the intracellular domain does not share significant homology with the other four members of this family (DCC/Neogenin/Punc/Nope).…”
Section: Discussionsupporting
confidence: 85%
“…The extracellular domain of Punc has the highest identity (43.8%) with that of Prtg. 25 The interaction between Prtg and Radil is mediated through the cytoplasmic domain of Prtg, as cytosolic domain-deleted Prtg (PrtgΔc) cannot associate with Radil (Figure 5c, lane 3).…”
Section: Resultsmentioning
confidence: 99%
“…Protogenin (PRTG) is a recently identified IgSF member in chick and mouse embryos (Toyoda et al, 2005;Vesque et al, 2006) and belongs to the DCC/neogenin subclass of IgSF. Unlike DCC and neogenin, the expression of which starts around midgestation (Gad et al, 1997), the expression of PRTG mRNA initiates immediately after gastrulation in mouse embryos and undergoes a sharp downregulation after embryonic day 10 (E10) (Vesque et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike DCC and neogenin, the expression of which starts around midgestation (Gad et al, 1997), the expression of PRTG mRNA initiates immediately after gastrulation in mouse embryos and undergoes a sharp downregulation after embryonic day 10 (E10) (Vesque et al, 2006). Recently, Wigg et al (2008) identified a possible association between PRTG and human attention deficit hyperactivity disorder.…”
Section: Introductionmentioning
confidence: 99%